DESIGNING OF ATTENUATION ELEMENTS AND CASCADES - MILLY, Miron (Trends in education, 2009)
The paper deals with a simple way of the L-network capacity-compensated resistance voltage dividers designing in the dividing cascades. The principle are based on impedance loading of the output gate of corresponding L-network divider by image impedance of the input gate of following L-network and by image impedance of load on the cascade end.
Keywords: voltage divider; dividing network (element; cell); attenuation cascade.